HARMONIZATION AND OBSTACLES IN THE IMPLEMENTATION OF INCLUSION EDUCATION AT INCLUSION PRIMARY SCHOOL IN BOGOR - Ai Juliani; Nenah Nurhasanah; Ahmad Hidayat; Elly Sukmanasa; Indri Yani (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2024)
This study aims to describe in detail the results of a field study conducted regarding the implementation of inclusion education at inclusion primary school in Bogor, which focuses on the positive things happening (harmonization) and the perceived limitations. The approach used in this study is a qualitative descriptive approach. In this study, the research instrument was the researcher himself. The research subjects in this case were school principals, four class teachers and five students. The sampling technique used is a targeted sampling technique. The data collection techniques used are interview techniques, observation and documentation. The data analysis technique used is Miles and Hubermen's model analysis technique which consists of several phases, namely data reduction, data presentation, as well as verification and conclusion. The results of the research show that there are alignment and obstacles in the implementation of inclusive education at SDN Perwira Bogor. The harmonization that is felt is a high sense of mutual respect, a good sense of understanding and cooperation with parents, which is very good. On the other hand, there are obstacles such as inadequate facilities and infrastructure, staff that do not meet needs and partnerships that still need to be improved.